1986
DOI: 10.1104/pp.82.4.1000
|View full text |Cite
|
Sign up to set email alerts
|

Apoplastic and Symplastic Pathways of Atrazine and Glyphosate Transport in Shoots of Seedling Sunflower

Abstract: ABSTRACII'4ClAtrazine (2-chloro4-lethylaminol-6-Iisopropylamino-s-triazine) and [4Clglyphosate (N-Iphosphonomethyllglycine) were xylem fed to sunflower shoots at 100 micromolar for 1 hour in the light, then placed in the dark at 100% relative humidity for 1, 4, 7, or 10 hours. The distribution of atrazine and glyphosate between shoot parts, in the leaves, and between the aoplast and symplast of the leaf was determined. The apoplastic concentrations and distribution patterns of atrazine and glyphosate in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0
4

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 32 publications
1
28
0
4
Order By: Relevance
“…They suggested that the negative charges associated with the cell wall and the negative membrane potential of the plasma membrane repel the anionic glyphosate molecule. Jachetta et al (1986) compared the uptake and translocation of atrazine and glyphosate and observed that glyphosate had limited access to the symplast of sunflower stem tissue when compared to the nonpolar atrazine. They attributed this difference to their relative lipid permeability .…”
mentioning
confidence: 99%
“…They suggested that the negative charges associated with the cell wall and the negative membrane potential of the plasma membrane repel the anionic glyphosate molecule. Jachetta et al (1986) compared the uptake and translocation of atrazine and glyphosate and observed that glyphosate had limited access to the symplast of sunflower stem tissue when compared to the nonpolar atrazine. They attributed this difference to their relative lipid permeability .…”
mentioning
confidence: 99%
“…In a simplified way, the movement of an herbicide within the plant can be accomplished by two main routes: apoplast and symplast. Apoplast is a group of dead cells -including cell walls, intercellular spaces, and xylem -which form a continuum where water and solutes have the ability to move (Jachetta, 1986). Symplast is defined as the total mass of living cells in a plant, which forms a long and complex net along the plant both through phloem and through direct connections between neighboring cells that are usually in the same organplasmodesmata (Hay, 1976).…”
Section: Herbicide Absorption and Translocationmentioning
confidence: 99%
“…In this situation, the herbicide moves freely among cells of the same domain because, in essence, "a single cytoplasm occurs" between cells of the same domain (Crawford & Zambryski, 2001). Penetration of these herbicides in a single cell enables their distribution to all other cells belonging to the same symplastic domain (Jachetta et al, 1986). In addition, plasmodesmata may have significant participation in translocation of molecules that have pKa (dissociation constant) below the pH of the xylem, which is approximately 5.5; it may also assist symplastic movement of these molecules by other routes besides phloem (Vidal, 2002).…”
Section: Herbicide Translocation Through Plasmodesmatamentioning
confidence: 99%
See 2 more Smart Citations